2020
DOI: 10.1111/ijn.12854
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organizational commitment, job satisfaction and workplace violence on turnover intention of emergency nurses: A cross‐sectional study

Abstract: Aims: To describe turnover intention of emergency nurses and clarify the effects of organizational commitment, job satisfaction and workplace violence on turnover intention. Background: Research has showed the predictors of turnover intention differed among nurses of different specialties. However, research on turnover intention has mostly focused on general nurses rather than emergency nurses. Design: A descriptive, cross-sectional study was conducted. Methods: A self-administered questionnaire was used to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 36 publications
5
46
0
2
Order By: Relevance
“…The results of first hypothesis testing revealed that there is a positive and significant impact of job satisfaction on organizational commitment (β=0.457, t= 13.484, p=0.000). The findings of the present study are consistent with the past studies (Li et al, 2020).…”
Section: Research Findingssupporting
confidence: 94%
“…The results of first hypothesis testing revealed that there is a positive and significant impact of job satisfaction on organizational commitment (β=0.457, t= 13.484, p=0.000). The findings of the present study are consistent with the past studies (Li et al, 2020).…”
Section: Research Findingssupporting
confidence: 94%
“…The 9-item Patient Health Questionnaire (PHQ-9): there are 9 items to evaluate and monitor the severity of depression, and the frequency of each symptom from 0 (no at all) to 3 (almost every day) in the past 2 weeks is scored on a 4-point scale. The total scores are as follows: lowest/no depression (0-4), mild depression (5-9), moderate depression (10)(11)(12)(13)(14), moderate-severe depression (15- 19) or severe depression (20)(21)(22)(23)(24)(25)(26)(27)(28). According to the total score, we classify depression into dichotomous variables by <10 (no or mild depression) of the PHQ-9 total score.…”
Section: Methodsmentioning
confidence: 99%
“…According to the frequency of each symptom in the past 2 weeks from 0 (no symptom at all) to 3 (almost every day), score each item on a 4-point scale. Elevated scores are classified as mild anxiety (5-9), moderate anxiety (10)(11)(12)(13)(14), and severe anxiety (15-21, 30). When the score is <10, we decide that there is no anxiety.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mahoney et al found that nurse job satisfaction among nurse anesthetists in the United States (US) had a direct negative effect on the propensity to leave ( 9 ). Li et al derived similar results while investigating the propensity of emergency nurses to leave and concluded that nurse job satisfaction should be improved to reduce the propensity ( 10 ). Qian et al found a positive effect of job satisfaction on nurse retention intentions in a sample of nurses from several hospitals ( 11 ).…”
Section: Introductionmentioning
confidence: 91%